Professional Self-Realization of Law Enforcement Officers at the Stage of Professional Training (Law and Safety, 2020)
The key concepts that assist to reflect the essence of the process of professional self-realization of police officers have been determined.The professional self-realization of the personality, which is determined by the value and sensory, intellectual and motivational features of the personality, has been studied. Modeling the experience of professional self-realization is the support of the personality for self-development of intellectual and volitional actions. This process is most productive in adolescence – at the time of completion of the development of readiness to choose a particular profession, defining oneself in a possible professional role. The main point of the studied process is the search for a professional image of “oneself”.It has been noted that the key stages of professional self-realization’s formation are: choice of educational institution, place of work (professional self-determination), subsequent choice of the type and direction of activity, formation within the chosen profession, professional growth, which reflects the effectiveness of professional self-realization. Thus, successful self-realization within the profession is based on a reasonable choice of place of study and future profession, continuous professional self-growth and self-development within labor activity, as well as satisfaction with the way of professional life and career.It has been studied that the development of the value sphere of the personality of law enforcement officers contributes to the optimization of their behavior and self-realization in such spheres of life as profession, family life, relationships, hobbies. The motivational component is one of the basic in the system of moral regulation of activities and behavior of professionals and includes a positive attitude to the chosen type of professional activity, the desire for self-realization and achievement, moral and professional attitudes and interests. Motivation acts as a link between the true goals, ideals, beliefs of the cadet and the actions, deeds, decisions he makes.The author has proved the expediency of forming value regulators of behavior and motivational sphere of future law enforcement officers in higher educational institutions with specific learning conditions, which may increase the efficiency of professional activity and self-realization of police officers in modern conditions.
Keywords: a police officer; professional self-realization; personal identity; motivational sphere; axiological sphere